Kuldiga, the City of the Future - Rappaport, Alexander (project baikal, 2019)
The local population composition in small historic towns will change. Even now, people that can work online settle down in such towns. These very people will save, revitalize and bring new blood in such towns as Kuldiga.
Keywords: small historic town; change in the population composition; online job; preservation; revitalization